2000
DOI: 10.4049/jimmunol.165.1.331
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Epitopes and Allergic Cross-Reactivity: Complex Formation Between a Fab Fragment of a Monoclonal Murine IgG Antibody and the Major Allergen from Birch Pollen Bet v 1

Abstract: The symptoms characteristic of allergic hypersensitivity are caused by the release of mediators, i.e., histamine, from effector cells such as basophils and mast cells. Allergens with more than one B cell epitope cross-link IgE Abs bound to high affinity FcεRI receptors on mast cell surfaces leading to aggregation and subsequent mediator release. Thus, allergen-Ab complexes play a crucial role in the cascade leading to the allergic response. We here report the structure of a 1:1 complex between the major birch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
222
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(233 citation statements)
references
References 40 publications
9
222
0
1
Order By: Relevance
“…Previously, the mAb BV16 raised against Bet v 1 was shown to compete with IgE binding to Bet v 1 [10]. Since BV16 recognizes homologous pollen allergens, but surprisingly did not cross-react with the homologous food allergens Pru av 1 and Api g 1.0101 (results not shown) in spite of the highly conserved interface [7,10], a panel of mAbs was raised against Pru av 1 and Bet v 1. The screening of their reactivity focused on binding to the P-loop region.…”
Section: Application Of Murine Mabsmentioning
confidence: 96%
See 2 more Smart Citations
“…Previously, the mAb BV16 raised against Bet v 1 was shown to compete with IgE binding to Bet v 1 [10]. Since BV16 recognizes homologous pollen allergens, but surprisingly did not cross-react with the homologous food allergens Pru av 1 and Api g 1.0101 (results not shown) in spite of the highly conserved interface [7,10], a panel of mAbs was raised against Pru av 1 and Bet v 1. The screening of their reactivity focused on binding to the P-loop region.…”
Section: Application Of Murine Mabsmentioning
confidence: 96%
“…The P-loop is one of three highly conserved regions on the surface of the Bet v 1 molecule proposed as IgE epitopes leading to cross-reactivity with pollen allergens of other trees of the Fagales order [5]. In the crystal structure of Bet v 1 in complex with a Fab fragment of the monoclonal murine IgG1 BV16, which was raised against Bet v 1 and partially inhibits binding of human IgE, the P-loop region constitutes the contact surface, with the side chain of Glu 45 located in a positively charged binding pocket forming two hydrogen bonds with the CDR3 (complementary determining region 3) of the heavy-chain variable domain [10]. These findings suggest the P-loop region around Glu 45 as one of the IgE epitopes of Bet v 1, and the introduction of four point mutations, including a mutation from Glu 45 to Ser, indeed reduced the IgE-binding capacity of Bet v 1 [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only method that can determine the complete structure of a B-cell epitope is preparation of a complex of a monoclonal antibody Fab fragment with its antigen, crystallization of this complex and determination of its structure, resolving those determinants recognized by the CDRs of the antibody on the native protein. Unfortunately, the only structural information about allergen Fab crystallization complexes derives from the co-crystallization of Bet v 1, the major birch (Betula verrucosa) pollen allergen, with a mouse monoclonal IgG 1 Fab fragment in a model system [5]. However, even this model epitope covering a buried surface of 931 Å 2 must be classified as discontinuous.…”
Section: About B-cell Epitopesmentioning
confidence: 99%
“…Studies of stinging insect venom allergens have shown that crossreactivity between allergens having <70% sequence identity is uncommon (13). Studies of inherent allergenicity and cross-reactivity have applications in the development of allergy immunotherapies and vaccines (14)(15)(16). Clinical and functional data for common allergens have been reported extensively and public databases contain entries of allergen sequences (17,18), structures (19), or T-cell epitopes (20,21).…”
mentioning
confidence: 99%